Ethylene vinyl acetate (EVA) alcoholysis method

By using alkaline anion exchange resin as a catalyst, the problems of metal ions introduced by NaOH catalysts, complex post-treatment and environmental pollution are solved, and the EVA alcoholylation reaction is efficient, green and environmentally friendly and economical.

CN119638878AActive Publication Date: 2025-03-18FUHAI (DONGYING) TECHNICAL SERVICES CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510158736.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-18
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The existing EVA alcoholylation method uses NaOH catalysts, which leads to metal ion residues, complex post-treatment and environmental pollution, making it difficult to effectively solve these problems.

Method used

The alkaline anion exchange resin is used as the catalyst, and the purification and activity of the catalyst are ensured through a series of rinsing and activation steps, and the alcoholylation reaction of EVA is carried out.

Benefits of technology

It realizes efficient progress of EVA alcoholylation reaction, reduces metal ion residues and post-treatment complexity, reduces environmental pollution, is simple in process, is green and environmentally friendly, and reduces the difficulty and cost of EVOH preparation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an alcoholysis method of EVA, and relates to the technical field of EVA. According to the technical scheme, the method comprises the following steps: S1, soaking and swelling alkaline anion exchange resin in deionized water; s2, washing the alkaline anion exchange resin in deionized water; s3, filling a chromatographic column with the washed alkaline anion exchange resin, and leaching with a hydrochloric acid solution; s4, washing the washed alkaline anion exchange resin with deionized water until the alkaline anion exchange resin is neutral, and then washing the alkaline anion exchange resin with a sodium hydroxide solution to obtain activated alkaline anion exchange resin; s5, enabling the EVA solution to pass through the activated alkaline anion exchange resin chromatographic column to obtain an EVOH crude product; and S6, washing the alcoholyzed EVOH crude product with water, carrying out vacuum drying, feeding the dried EVOH crude product into extrusion equipment, and carrying out grain-sized dicing and cleaning to obtain the EVOH resin. According to the method, the problems that metal impurities are introduced into a NaOH catalyst, the post-treatment process is complicated and environmental pollution is caused are solved, and the preparation difficulty and cost of EVOH are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of EVA, in particular to an alcoholysis method of EVA. Background Art

[0002] Ethylene-vinyl alcohol copolymer (EVOH) is a polymer material with special properties. It is a crystalline polymer with a chain structure. EVOH combines the good processability of ethylene polymers and the extremely high gas barrier properties of vinyl alcohol polymers, and is a new type of high barrier material. On the one hand, the gas barrier property of EVOH is 10,000 times that of similar commonly used products PE, so it can effectively extend the shelf life and fragrance preservation period of food; on the other hand, it has excellent physical properties, good transparency, glossiness, mechanical properties, etc., is easy to shape and process, and can be made into products of various shapes and sizes. In addition, EVOH does not contain chlorine and dioxins, waste can be recycled, and carbon dioxide and water are produced when incinerated. It is an excellent packaging material, and is widely used in packaging materials, automotive fields, medical fields, etc.

[0003] Conventional EVOH preparation methods generally involve alcoholysis of ethylene-vinyl acetate copolymer (EVA). Traditional alcoholysis reactions usually use NaOH as a catalyst, but this method has many shortcomings: 1) Metal ion residues: NaOH catalysts may introduce metal ions during the reaction, which are difficult to remove and will affect the purity and performance of the product; 2) Complex post-processing: When using NaOH as a catalyst, complex subsequent processing steps are required, such as neutralization, washing, and drying of the EVOH product, which increases production costs and process complexity; 3) Environmental pollution: The use and subsequent treatment of NaOH catalysts may produce wastewater, waste gas, and waste residue, which may cause certain pollution to the environment. Therefore, finding a catalyst to replace NaOH to overcome the above shortcomings has become an urgent problem to be solved in this field. Summary of the invention

[0004] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide an alcoholysis method for EVA, to adopt an alkaline anion exchange resin as a catalyst, to solve the problems that a NaOH catalyst may introduce metal impurities, the post-treatment process is complicated and may cause environmental pollution, the process is simple, green and environmentally friendly, and the difficulty and cost of preparing EVOH are greatly reduced.

[0005] The technical solution of the present invention is: The alcoholysis method of EVA comprises the following steps: S1: soaking and swelling the alkaline anion exchange resin in deionized water; S2 washing the swollen basic anion exchange resin in deionized water; S3: Load the washed alkaline anion exchange resin into the chromatography column and elute it with 1-6 mol / L hydrochloric acid solution until there is no Fe in the eluent. 3+ , Cu 2+ Mg 2+ impurities, and appears as a colorless solution macroscopically; at this time, the fixed cation of the alkaline anion exchange resin is still a quaternary ammonium group, and the anion group has been replaced by Cl after eluting with hydrochloric acid solution. - ; S4: After washing the washed alkaline anion exchange resin with deionized water until it is neutral, it is then washed with a 1-10 mol / L sodium hydroxide solution to obtain an activated alkaline anion exchange resin; at this time, the fixed cation of the alkaline anion exchange resin is a quaternary ammonium group, and the anion group is converted back to OH after being washed with the sodium hydroxide solution. - During the entire elution process of steps S3 and S4, the residual metal ions are first washed with hydrochloric acid solution, then washed with deionized water until neutral, and then washed with sodium hydroxide solution until the anion groups of the alkaline anion exchange resin are converted back to OH - ; During the elution process of sodium hydroxide solution, Cl - The eluent is essentially a mixed solution of sodium hydroxide and sodium chloride, which can be determined by titrating Cl - Or detect the pH of the eluent to determine whether all anions on the alkaline anion exchange resin have been replaced by OH - ; S5: passing the EVA solution through an activated alkaline anion exchange resin chromatography column to cause the EVA to undergo alcoholysis to obtain a crude EVOH product; The crude EVOH after S6 alcoholysis is washed with water and vacuum dried before entering the extrusion equipment, and then pelletized and cleaned to obtain EVOH resin.

[0006] Preferably, in step S1, the alkaline anion exchange resin is 201×7MBFC, D201 or LH-400Cl alkaline anion exchange resin; the soaking and swelling time is 6-12 hours. The fixed cationic group of the 201×7MBFC alkaline anion exchange resin is a quaternary ammonium group, which can adsorb and exchange anions with negative charges, and the exchange anion group is OH - , used to capture acidic substances and acidic ions; D201 and LH-400Cl alkaline anion exchange resins have fixed cationic groups as quaternary ammonium groups, which can adsorb and exchange negatively charged anions, and the exchange anion groups are Cl - , used to capture acidic substances and acidic ions.

[0007] Preferably, in step S5, the concentration of the EVA solution is 4-25wt.%.

[0008] Preferably, in step S5, the alcoholysis reaction temperature is 40-70° C., and the flow rate of the EVA solution in the activated alkaline anion exchange resin chromatography column is 1-80 mL / h.

[0009] Preferably, in step S5, the EVA solution is sequentially passed through three activated alkaline anion exchange resin chromatography columns, and a continuous stirring reactor with stirring and heating functions is arranged between the chromatography columns.

[0010] Preferably, the method further comprises step S7, wherein the alkaline anion exchange resin used in step S5 is activated using a good solvent, deionized water and sodium hydroxide solution in sequence to restore its catalytic activity and retain it for repeated use; if the alkaline anion exchange resin used in step S5 is used for the first time, steps S1-S4 need to be performed; if the alkaline anion exchange resin used in step S5 is treated in step S7, steps S1-S4 are not performed and the resin is directly used in step S5.

[0011] Preferably, in step S7, the good solvent is tetrahydrofuran or N,N-dimethylformamide.

[0012] Preferably, in step S7, the concentration of the sodium hydroxide solution is 1-10 mol / L.

[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The alkaline anion exchange resin of the present invention has alkaline anion exchange groups on its surface, which can change the charge state and reaction activity of the reactants, thereby reducing the activation energy of the reaction and accelerating the reaction efficiency, thereby achieving the alcoholysis reaction of EVA. The alkaline anion exchange groups are mainly quaternary ammonium groups, which dissociate into OH in water. - It is strongly alkaline and can be adsorbed and combined with anions in the solution, thereby producing anion exchange. In addition, after the present invention uses alkaline anion exchange resin instead of NaOH catalyst, no metal ions are introduced and no post-treatment is required. It not only simplifies the EVA alcoholysis process, but also reduces the amount of solvent and pure water used in the post-treatment process, which is green, environmentally friendly, and economical.

[0014] 2. After use, the alkaline anion exchange resin of the present invention can be activated, recovered and reused, which greatly reduces the production cost. DETAILED DESCRIPTION

[0015] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0016] Example 1 The alcoholysis method of EVA of the present embodiment comprises the following steps: S1 Take 20 parts of 201×7MBFC alkaline anion exchange resin and put them into sufficient deionized water to soak and swell for 10 hours; S2: washing the swollen 201×7MBFC alkaline anion exchange resin in deionized water to remove surface and soluble impurities; S3: Load the washed 201×7MBFC alkaline anion exchange resin into the chromatography column and elute it with 1 mol / L hydrochloric acid solution at a flow rate of 4 mL / min until there is no Fe in the eluent. 3+ , Cu 2+ Mg 2+ etc. impurities, macroscopically appearing as a colorless solution; S4 washed the 201×7MBFC alkaline anion exchange resin with deionized water until it was neutral, and then washed with 1 mol / L sodium hydroxide solution at a flow rate of 4 mL / min to obtain the activated 201×7MBFC alkaline anion exchange resin. The anions were exchanged into OH - ; S5: Fill the activated 201×7MBFC alkaline anion exchange resin into three chromatography columns A, B, and C. The inner diameter of the chromatography column is 26 mm, the height is 20 cm, and it is equipped with an insulation layer. The temperature of the insulation layer is 50°C. A methanol solution of EVA with a concentration of 25 wt.% is washed from bottom to top at a rate of 24 mL / h. The solution passes through the three chromatography columns in sequence to make the EVA undergo alcoholysis reaction. A continuous stirred reactor (CSTR) with stirring and heating functions is provided between the chromatography columns to remove the methyl acetate by-product generated by the methanol ester exchange reaction during the reaction. The overflow volume of the CSTR is 500 mL, the top is open and equipped with a condensation recovery device, the heating temperature is 60°C, and the stirring rate is 200 rpm. After the EVA solution is subjected to three alcoholysis catalyzed by the 201×7MBFC alkaline anion exchange resin, the alcoholysis degree can reach 99.5%, and a crude EVOH product is obtained. The crude EVOH product after alcoholysis in S6 is washed with water and vacuum dried before entering the extrusion equipment. It is then pelletized and cleaned to obtain EVOH resin. No obvious yellowing or other color spots are found in the EVOH resin. In S7, tetrahydrofuran is first used to dissolve and remove the alkaline anion exchange resin remaining in the chromatography column, and then deionized water and 1 mol / L sodium hydroxide solution are used to wash and remove the acetate ions in the alkaline anion exchange resin, and the flow rate of the sodium hydroxide solution is 4 mL / min; the alkaline anion exchange resin finally obtained can be used as an alcoholysis catalyst for EVA again, and is applied to participate in the alcoholysis of EVA in step S5. The alcoholysis degree of EVA is 99.6%, indicating that the alkaline anion exchange resin can be repeatedly recycled and will not affect the alcoholysis reaction of EVA, thereby reducing production costs and saving solvents.

[0017] Example 2 The alcoholysis method of EVA of the present embodiment comprises the following steps: S1 Take 20 parts of D201 basic anion exchange resin and soak it in sufficient deionized water to swell for 12 hours; S2: washing the swollen D201 alkaline anion exchange resin in deionized water to remove surface and soluble impurities; S3: The washed D201 alkaline anion exchange resin is loaded into the chromatography column and eluted with 6 mol / L hydrochloric acid solution at a flow rate of 4 mL / min until there is no Fe in the eluent. 3+ , Cu 2+ Mg 2+ etc. impurities, macroscopically appearing as a colorless solution; S4 washed the D201 alkaline anion exchange resin with deionized water until it was neutral, and then washed with 10 mol / L sodium hydroxide solution at a flow rate of 4 mL / min to obtain the activated D201 alkaline anion exchange resin. The anions were exchanged into OH - ; S5 fills the activated D201 alkaline anion exchange resin into three chromatography columns A, B, and C. The inner diameter of the chromatography column is 26 mm, the height is 20 cm, and it is equipped with an insulation layer. The temperature of the insulation layer is 70°C. A methanol solution of EVA with a concentration of 12 wt.% is washed from bottom to top at a rate of 80 mL / h. The solution passes through the three chromatography columns in sequence to make the EVA undergo alcoholysis reaction. A continuous stirred reactor (CSTR) with stirring and heating functions is arranged between the chromatography columns to remove the methyl acetate by-product generated by the methanol ester exchange reaction during the reaction. The overflow volume of the CSTR is 500 mL, the top is open and equipped with a condensation recovery device, the heating temperature is 60°C, and the stirring rate is 200 rpm. After the EVA solution undergoes alcoholysis catalyzed by the D201 alkaline anion exchange resin three times, the alcoholysis degree can reach 99.2%, and the crude EVOH product is obtained. The crude EVOH product after alcoholysis in S6 is washed with water and vacuum dried before entering the extrusion equipment. It is then pelletized and cleaned to obtain EVOH resin. No obvious yellowing or other color spots are found in the EVOH resin. In S7, tetrahydrofuran is first used to dissolve and remove the alkaline anion exchange resin remaining in the chromatography column, and then deionized water and 10 mol / L sodium hydroxide solution are used to wash and remove the acetate ions in the alkaline anion exchange resin, and the flow rate of the sodium hydroxide solution is 4 mL / min; the alkaline anion exchange resin finally obtained can be used as an alcoholysis catalyst for EVA again, and is applied to participate in the alcoholysis of EVA in step S5. The alcoholysis degree of EVA is 99.3%, indicating that the alkaline anion exchange resin can be repeatedly recycled and will not affect the alcoholysis reaction of EVA, thereby reducing production costs and saving solvents.

[0018] Example 3 The alcoholysis method of EVA of the present embodiment comprises the following steps: S1 Take 20 parts of LH-400CL alkaline anion exchange resin and soak them in sufficient deionized water for 6 hours; S2: washing the swollen LH-400CL alkaline anion exchange resin in deionized water to remove surface and soluble impurities; S3: Load the washed LH-400CL alkaline anion exchange resin into the chromatography column and elute it with 3 mol / L hydrochloric acid solution at a flow rate of 4 mL / min until there is no Fe in the eluent. 3+ , Cu 2+ Mg 2+ etc. impurities, macroscopically appearing as a colorless solution; S4: After washing the washed LH-400CL alkaline anion exchange resin with deionized water until it is neutral, it is then washed with a 5 mol / L sodium hydroxide solution at a flow rate of 4 mL / min to obtain an activated LH-400CL alkaline anion exchange resin. - ; S5: Fill the activated LH-400CL alkaline anion exchange resin into three chromatography columns A, B, and C. The inner diameter of the chromatography column is 26 mm, the height is 20 cm, and the column is provided with an insulation layer. The temperature of the insulation layer is 40°C. A methanol solution of EVA with a concentration of 4wt.% is washed from bottom to top at a rate of 1 mL / h. The solution passes through the three chromatography columns in sequence to make the EVA undergo alcoholysis reaction. A continuous stirred reactor (CSTR) with stirring and heating functions is provided between the chromatography columns to remove the methyl acetate by-product generated by the methanol ester exchange reaction during the reaction. The overflow volume of the CSTR is 500 mL, the top is open and provided with a condensation recovery device, the heating temperature is 60°C, and the stirring rate is 200 rpm. After the EVA solution is catalyzed by alcoholysis with LH-400CL alkaline anion exchange resin for three times, the alcoholysis degree can reach 99.4%, and the crude EVOH product is obtained. The crude EVOH product after alcoholysis in S6 is washed with water and vacuum dried before entering the extrusion equipment. It is then pelletized and cleaned to obtain EVOH resin. No obvious yellowing or other color spots are found in the EVOH resin. In S7, N,N-dimethylformamide is first used to dissolve and remove the residual alkaline anion exchange resin in the chromatography column, and then deionized water and 5 mol / L sodium hydroxide solution are used to wash and remove the acetate ions in the alkaline anion exchange resin, and the flow rate of the sodium hydroxide solution is 4 mL / min; the alkaline anion exchange resin finally obtained can be used as an alcoholysis catalyst for EVA again, and is applied to participate in the alcoholysis of EVA in step S5. The alcoholysis degree of EVA is 99.3%, indicating that the alkaline anion exchange resin can be repeatedly recycled and will not affect the alcoholysis reaction of EVA, thereby reducing production costs and saving solvents.

[0019] Comparative Example 1 The difference from Example 1 is that step S3 is not performed.

[0020] In the final step S5, the alcoholysis degree of EVA is 98.2%; the EVOH resin obtained in step S6 has red and yellow spots, which are analyzed to be Fe 3+ , Cu 2+ The precipitate color of metal ions in alkaline solution; in step S7, the alcoholysis degree of EVA is 98.5%, and red and yellow spots also exist in the EVOH resin.

[0021] Comparative Example 2 The difference from Example 1 is that step S4 is not performed, and in step S7, only a good solvent and deionized water are used to wash the alkaline anion exchange resin, and no sodium hydroxide solution is used to wash the alkaline anion exchange resin.

[0022] In the final step S5, the alcoholysis degree of EVA is 65.2%, and no red, yellow or other color spots are found in the EVOH resin; in step S7, the alcoholysis degree of EVA is 34%, and no red, yellow or other color spots are found in the EVOH resin. This is because the anions of the alkaline anion exchange resin are all OH - In Comparative Example 2, since the alkaline anion exchange resin was not eluted with sodium hydroxide solution, part of the negative ions of the alkaline anion exchange resin were Cl - , basic anion exchange resin is weakly alkaline or weakly acidic, resulting in weak alcoholysis catalytic activity.

[0023] Comparative Example 3 The difference from Example 1 is that in step S5, only two chromatography columns A and B are provided, and a CSTR is provided between the two chromatography columns.

[0024] In the final step S5, the alcoholysis degree of EVA is 98.2%, and no obvious red, yellow or other color spots are found in the EVOH resin; in step S7, the alkaline anion exchange resin finally obtained is used to participate in the alcoholysis of EVA in step S5, and only two chromatography columns and one CSTR are used, and the alcoholysis degree of EVA is 98.4%, and no obvious red, yellow or other color spots are found in the EVOH resin. This shows that the alcoholysis reaction of EVA basically completes most of the reaction in the two alkaline anion exchange resin chromatography columns, and the third alkaline anion exchange resin chromatography column can further improve the alcoholysis degree of EVA.

[0025] Comparative Example 4 The difference from Example 1 is that in step S3, the concentration of the hydrochloric acid solution is 0.01 mol / L.

[0026] In the final step S5, the alcoholysis degree of EVA is 99.4%, and the EVOH resin has red and yellow spots; in step S7, the alcoholysis degree of EVA is 99.2%, and the EVOH resin also has red and yellow spots. This is because when the concentration of the hydrochloric acid solution is too low, it may be impossible to remove the Fe and Cu element impurities in the alkaline anion exchange resin for a long time. These element impurities will produce colored precipitates when washed with sodium hydroxide. These colored precipitates are the cause of the red and yellow spots in the EVOH resin.

[0027] Comparative Example 5 The difference from Example 1 is that in step S4, the concentration of the sodium hydroxide solution is 0.02 mol / L.

[0028] In the final step S5, the alcoholysis degree of EVA is 54.2%, and the EVOH resin does not have red, yellow and other color spots; in step S7, the alcoholysis degree of EVA is 22.7%, and the EVOH resin also does not have red, yellow and other color spots. This is because when the concentration of the sodium hydroxide solution is too low, eluting the alkaline anion exchange resin with sodium hydroxide solution for a certain period of time may cause Cl in the alkaline anion exchange resin - Cannot be replaced by OH - , which may cause the alkaline anion exchange resin to be unable to have extremely strong alkalinity, thus affecting the degree of alcoholysis.

[0029] Comparative Example 6 The difference from Example 1 is that in step S5, the methanol solution of EVA is replaced by the isopropanol solution of EVA, and the temperature of the insulation layer is 80°C.

[0030] In the final step S5, the alcoholysis degree of EVA is 99.6%, and the EVOH resin shows yellow spots; in step S7, the alcoholysis degree of EVA is 99.3%, and the EVOH resin also shows yellow spots. This is because the alcoholysis reaction temperature is too high and the alcoholysis rate is too fast. The alcoholysis may be completed in the early stage of the alkaline anion exchange resin chromatography column. When the middle section is kept at high temperature, the EVOH resin is oxidized, which causes it to turn yellow.

[0031] Comparative Example 7 The difference from Example 1 is that in step S7, the concentration of the sodium hydroxide solution is 0.02 mol / L.

[0032] In the final step S5, the alcoholysis degree of EVA is 99.5%, and the EVOH resin has no red or yellow impurities; in step S7, the alcoholysis degree of EVA is 32.7%, and the EVOH resin has no red or yellow impurities. This is because when the concentration of the sodium hydroxide solution is too low, the activation of the alkaline anion exchange resin may cause the Cl in the alkaline anion exchange resin to - Cannot be replaced by OH - , which may cause the alkaline anion exchange resin to be unable to have extremely strong alkalinity, thus affecting the degree of alcoholysis.

Claims

1. A method for alcoholysis of EVA, characterized in that: The following steps are involved: S1: soaking and swelling the alkaline anion exchange resin in deionized water; S2 washing the swollen basic anion exchange resin in deionized water; S3: loading the washed alkaline anion exchange resin into a chromatography column and eluting it with a 1-6 mol / L hydrochloric acid solution; S4: washing the washed alkaline anion exchange resin with deionized water until it is neutral, and then washing it with a 1-10 mol / L sodium hydroxide solution to obtain an activated alkaline anion exchange resin; S5: passing the EVA solution through an activated alkaline anion exchange resin chromatography column to cause the EVA to undergo alcoholysis to obtain a crude EVOH product; The crude EVOH after S6 alcoholysis is washed with water and vacuum dried before entering the extrusion equipment, and then pelletized and cleaned to obtain EVOH resin.

2. The alcoholysis method of EVA as claimed in claim 1, characterized in that In step S1, the alkaline anion exchange resin is 201×7MBFC, D201 or LH-400Cl alkaline anion exchange resin; and the soaking and swelling time is 6-12 hours.

3. The alcoholysis method of EVA as claimed in claim 1, characterized in that, In step S5, the concentration of the EVA solution is 4-25wt.%.

4. The alcoholysis method of EVA as claimed in claim 1, characterized in that In step S5, the alcoholysis reaction temperature is 40-70° C., and the flow rate of the EVA solution in the activated alkaline anion exchange resin chromatography column is 1-80 mL / h.

5. The alcoholysis method of EVA as claimed in claim 1, characterized in that, In step S5, the EVA solution is sequentially passed through three activated alkaline anion exchange resin chromatography columns, and a continuous stirring reactor with stirring and heating functions is arranged between the chromatography columns.

6. The alcoholysis method of EVA as claimed in claim 1, characterized in that, The method further includes step S7, wherein the alkaline anion exchange resin used in step S5 is activated using a good solvent, deionized water and sodium hydroxide solution in sequence to restore its catalytic activity and retain it for repeated use; if the alkaline anion exchange resin used in step S5 is the first alkaline anion exchange resin, steps S1-S4 need to be performed; if the alkaline anion exchange resin used in step S5 is the alkaline anion exchange resin treated in step S7, steps S1-S4 are not performed and the resin is directly used in step S5.

7. The alcoholysis method of EVA as claimed in claim 6, characterized in that In step S7, the good solvent is tetrahydrofuran or N,N-dimethylformamide.

8. The alcoholysis method of EVA as claimed in claim 6, characterized in that In step S7, the concentration of the sodium hydroxide solution is 1-10 mol / L.

Citation Information

Patent Citations

  • Preparation method of high-temperature-resistant strongly-alkaline anion exchange resin

    CN112125991A

  • Preparation method and device of polyvinyl alcohol with high alcoholysis degree

    CN114276478A

  • Method and device for improving alcoholysis degree of polyvinyl alcohol

    CN114349884A

  • Method for improving alcoholysis degree of polyvinyl alcohol

    CN118165146A

  • Method for improving alcoholysis degree of polyvinyl alcohol

    CN118165147A